MicroRNA 10a induces glioma tumorigenesis by targeting myotubularin‐related protein 3 and regulating the Wnt/β‐catenin signaling pathway. (11th April 2019) - Yan, Yan; Yan, Hua; Wang, Qin; Zhang, Le; Liu, Ying; Yu, Haimiao
Abstract : MicroRNAs are involved in the regulation of tumor formation. A previous study suggested that miR‐10a promotes glioma cell migration and invasion. However, the effect of miR‐10a on the proliferation of glioma cells remains unknown. In this study, we demonstrated that miR‐10a promoted proliferation and reduced apoptosis in glioma cells by directly targeting the 3′‐UTR of myotubularin‐related protein 3 (MTMR3). miR‐10a enhanced, while MTMR3 weakened, the growth of glioma in vivo . Ectopic expression of MTMR3 neutralized the effect of miR‐10a on glioma. Furthermore, miR‐10a and MTMR3 regulated β‐catenin expression and genes downstream of the Wnt/β‐catenin signaling pathway, such as Bcl‐2, c‐myc, p‐c‐Jun, and cleaved caspase‐3, to affect the proliferation ability and apoptosis of glioma cells. In conclusion, our results indicated that miR‐10a regulated cell proliferation and apoptosis by directly targeting MTMR3 and could function as a prognostic factor for progression of glioma. Abstract : miRNAs are involved in the regulation of tumor formation. miR‐10a was previously shown to regulate glioma cell invasion and migration, but its role in regulation of glioma cell proliferation was not investigated. Here, we found that miR‐10a and its target gene myotubularin‐related protein 3 (MTMR3) regulated the Wnt/β‐catenin signaling pathway. Furthermore, miR‐10a regulated cell proliferation and apoptosis by directly targeting MTMR3 and could function as a prognostic factor for progression of glioma.